Understanding the Effects of Nanoporous Titanium on Osteoblastic Cells in Hyperglycemic Conditions - Agrawal, Nidhi Narendra (Université d'Ottawa / University of Ottawa, 2023)
Towards the creation of the next generation of biomedical implants that effectively integrate in tissues, understanding cell behaviour at the material-host interface to control and optimize the biological outcome is a crucial endeavour. It is now well known that the nanoscale surface properties of biomaterials play a significant role in directing the activity of adherent cells at the implant-host tissue interface. A variety of cellular functions, ranging from adhesion and proliferation to differentiation along specific lineages, are guided by the nanoscale topographical and physicochemical features of the substrate. This evidence reaffirms the role of surface features on eliciting an enhanced response of cells towards improved biological outcomes (e.g., bone integration) of implanted biomaterials. In this context, Titanium (Ti) and its alloys are popular biomaterials widely used in orthopedic, dental, and cardiovascular applications. In particular, in the field of osseointegrated devices, chemical treatments of titanium, specifically oxidative nanopatterning (i.e., a simple yet effective treatment with a H₂SO₄/H₂O₂ solution), have shown to be a promising strategy for guiding and controlling the fate of relevant cells (e.g., osteoblasts, stem cells), thereby achieving the ability to direct the biological response towards the desired outcome. In this context, the sponge-like nanoporous surface resulting from oxidative nanopatterning of titanium allows direct surface cueing to bone cells. It also has the capacity to selectively regulate cell behaviour, modulate the expression of crucial determinants of cell activity, and offers the potential to harness the power of stem cells. However, the mechanisms that control how cells sense and respond to these nanometric cues are still elusive. A novel strategy to elucidate them takes inspiration from in-vivo protocols, where "knock-out" animal models are used to determine the role of a specific gene. Based on this, I propose an original approach aimed at investigating cell response under conditions known to affect specific cellular processes, thereby determining whether these activities can be rescued by direct cueing by the substrate, ultimately elucidating their implication in responding to a given nanostructured substrate. In particular, hyperglycemic culturing conditions often used to mimic diabetes in-vitro are known to exert detrimental effects on the proliferation and differentiation of osteoblasts, and thereby could be an excellent opportunity to test whether the nanometric surface features resulting from oxidative nanopatterning of titanium also possess the ability to compensate to the cell-level changes caused by higher levels of glucose. This would ultimately demonstrate a direct effect of the substrate on these events and help us understand the mechanisms involved in cell-biomaterial interactions. To address this challenge, I propose to investigate the response of human MG-63 osteoblastic cells to nanoporous titanium under hyperglycemic conditions. The goal is, therefore, to understand whether direct nanotopographical cueing at the nanoscale can rescue MG-63 cells from the effects of hyperglycemia, thereby casting new light on the mechanisms underlying the interactions between this widely used cell line and nanoporous titanium. In parallel, results from my work aim at providing new fundamental evidence to interpret results from that body of literature that uses high glucose content as a way to mimic the osseointegration of biomaterials in diabetic conditions.
Keywords: Hyperglycemia; Titanium; Biomaterials; Oxidative Nanopatterning